2019
DOI: 10.3856/vol47-issue3-fulltext-10
|View full text |Cite
|
Sign up to set email alerts
|

Oogenesis of Lithodes santolla: histological and histochemical characterization

Abstract: Although Lithodes santolla is a resource with high commercial importance that has aroused interest in controlled reproduction in captivity, currently, little knowledge is available about basic reproductive aspects of this species. This research study describes detailed oogenesis stages at the histological level in adult females of the southern king crab of the Magellan and Chilean Antarctic Region. Oogenesis was quantitatively analyzed from the proliferation of 10-24 μm oogonia and during oocyte growth. Five s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…The early vitellogenic oocytes, which were present in Stage II and observed with light microscopy, have been described in TEM by Mollemberg et al (2017), who reported that in other Majoidea, no evidence of the chorion was observed, and oocytes were surrounded by follicular cells. Our observation that triglycerides increase and phospholipids decrease during vitellogenesis and post-vitellogenesis is consistent with patterns observed by Arcos-Ortega et al (2019) in The description of ovarian development in this study used quantitative and qualitative characteristics of histological and histochemical analyses, which were similar to methods used in other species of decapod crustaceans, such as the shrimp Penaeus japonicus (Yano, 1988), the lobster Panulirus japonicus (Minagawa & Sano, 1997), the anomuran crab Clibanarius clibanarius (Varadarajan & Subramoniam, 1980), and the brachyuran crab Travancoriana schirnerae (Smija & Sudha, 2015) to describe gonadal development.…”
supporting
confidence: 88%
See 2 more Smart Citations
“…The early vitellogenic oocytes, which were present in Stage II and observed with light microscopy, have been described in TEM by Mollemberg et al (2017), who reported that in other Majoidea, no evidence of the chorion was observed, and oocytes were surrounded by follicular cells. Our observation that triglycerides increase and phospholipids decrease during vitellogenesis and post-vitellogenesis is consistent with patterns observed by Arcos-Ortega et al (2019) in The description of ovarian development in this study used quantitative and qualitative characteristics of histological and histochemical analyses, which were similar to methods used in other species of decapod crustaceans, such as the shrimp Penaeus japonicus (Yano, 1988), the lobster Panulirus japonicus (Minagawa & Sano, 1997), the anomuran crab Clibanarius clibanarius (Varadarajan & Subramoniam, 1980), and the brachyuran crab Travancoriana schirnerae (Smija & Sudha, 2015) to describe gonadal development.…”
supporting
confidence: 88%
“…Tukey's test (α = .05) showed significant differences among all substages of oocytes, except for oocytes in the Pvo and Gvb substages (Figure 6). vannamei (Corral-Rosales et al, 2018), and in L. santolla (Arcos-Ortega et al, 2019). In these studies, the lipids that were part of the yolk and membranes were preserved and coverage area of stained lipids was quantified through digital image analysis, following methods of Rodríguez-Jaramillo et al (2008).…”
Section: Analysis Of Oocyte Size Changes During Gonadal Development In Femalesmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipids stored in the midgut gland are transferred to the ovary during the vitellogenesis [66]. The polar lipids (phospholipids) are mainly responsible for the increase of lipid concentration of the ovaries during primary vitellogenesis [67,68], while the triglycerides increase during secondary vitellogenesis [68]. The profile of fatty acids present in the maturing ovaries is a reflection of the fatty acid requirement of that tissue or the requirements for the developing embryos after fertilization [67].…”
Section: Plos Onementioning
confidence: 99%